The Challenges of The Society 5.0 Era: The Evaluation of Learning in Primary Education - Dina Oktaviana; Ahmad Barizi; Mohamad Zubad Nurul Yaqin (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2022)
Learning evaluation is an important thing in influencing education in the digital era and in facing the era of society 5.0. This research aims to describe how the evaluation of learning towards education in facing the challenges of society 5.0 era. The type of research used is literature review, by collecting data or theoretical materials from various scientific journal references or previous research through 3 important processes. The data collection technique uses library research with sources from journals, scientific articles, and books. Data analysis techniques obtained from reference materials from books, journals and scientific articles are used to prove the data regarding evaluation in the 5.0 era which is expected to be able to provide comprehensive and in-depth facts about the form of evaluation in dealing with education in the era of society 5.0. The results show that learning evaluation is one of the major influences in the development of education that can be used as material in facing the era of society 5.0. Learning evaluation is also needed in every lesson to develop better learning designs so as to produce students who think critically and creatively in solving problems and are able to keep up with the times.